2021
DOI: 10.22603/ssrr.2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcome and Predictors of Therapeutic Effects of Intradiscal Condoliase Injection for Patients with Lumbar Disc Herniation

Abstract: Hideaki Nakajima: conception and design various aspects of the study, acquisition of patients, analysis and interpretation of data, drafting of the manuscript; Arisa Kubota: analysis and interpretation of data, statistical analysis; Yasuhisa Maezawa: conception and design of the study, acquisition of patients; Shuji Watanabe: analysis and interpretation of data, statistical analysis; Kazuya Honjoh: analysis and interpretation of data, statistical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 30 publications
(24 reference statements)
4
31
0
Order By: Relevance
“…The main finding of the present study was that calcified or ossified herniation was a risk factor for unsuccessful treatment with chemonucleolysis using condoliase. Previous studies demonstrated that 70-85% of patients achieved >50% improvement of NRS or visual analogue scale scores at 3 months after chemonucleolysis with condoliase [15,[21][22][23][24]. The present study showed that >80% of patients were classified into the G-group (without requirement for additional surgery), and that the mean NRS scores of leg pain and leg numbness significantly improved by 63.9% and 64.4%, respectively, at 3 months, which was comparable with previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…The main finding of the present study was that calcified or ossified herniation was a risk factor for unsuccessful treatment with chemonucleolysis using condoliase. Previous studies demonstrated that 70-85% of patients achieved >50% improvement of NRS or visual analogue scale scores at 3 months after chemonucleolysis with condoliase [15,[21][22][23][24]. The present study showed that >80% of patients were classified into the G-group (without requirement for additional surgery), and that the mean NRS scores of leg pain and leg numbness significantly improved by 63.9% and 64.4%, respectively, at 3 months, which was comparable with previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…30 While it has been reported that higher rates of improvement for lower Pfirrmann classifications, 30 , 31 Oshita et al reported that condoliase appeared more effective for patients with Pfirrmann grade IV compared to grade III patients. 32 , 33 , 34 Regardless of the therapeutic effect of condoliase, we selected patients with Pfirrmann grade III, apart from one of the 12 patients in this study. However, we did not evaluate the action of condoliase on the nucleus pulposus clinically, for example, measurement of the hernia size before and after condoliase administration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the real-world effectiveness of CC for LDH [3,5,6,8,9]. The efficacy rate of CC has been reported to be 62%-75% at 3 months and 77%-85% at 6 months after treatment.…”
Section: Discussionmentioning
confidence: 99%